Digital Module 10: Rasch Measurement Theory https://ncme.elevate.commpartners.com. Issue 4 (8th December 2019) - Wang, Jue; Engelhard, George
Abstract: In this digital ITEMS module, Dr. Jue Wang and Dr. George Engelhard Jr. describe the Rasch measurement framework for the construction and evaluation of new measures and scales. From a theoretical perspective, they discuss the historical and philosophical perspectives on measurement with a focus on Rasch's concept of specific objectivity and invariant measurement. Specifically, they introduce the origins of Rasch measurement theory, the development of model‐data fit indices, as well as commonly used Rasch measurement models. From an applied perspective, they discuss best practices in constructing, estimating, evaluating, and interpreting a Rasch scale using empirical examples. They provide an overview of a specialized Rasch software program ( Winsteps ) and an R program embedded within Shiny ( Shiny_ERMA ) for conducting the Rasch model analyses. The module is designed to be relevant for students, researchers, and data scientists in various disciplines such as psychology, sociology, education, business, health, and other social sciences. It contains audio‐narrated slides, sample data, syntax files, access to Shiny_ERMA program, diagnostic quiz questions, data‐based activities, curated resources, and a glossary.